EVT571: Environmental Remote Sensing / Faculty of Applied Sciences - UiTM, Faculty of Applied Sciences (Universiti Teknologi MARA (UiTM), 2020)
This course is designed to introduce students to remote sensing of the environment by discussing the fundamental characteristic of electromagnetic radiation, energy interactions with the atmosphere and Earth’s surface and ways to extract meaningful geophysical information from remote sensing data to solve environmental problems. Digital image processing techniques and algorithms involved in the measurement, analysis and interpretation of electromagnetic energy collected by remote sensing instruments are demonstrated through in practical class and hands on exercise using the image processing system/software. The goal is for students to develop an understanding of inventorying, mapping and monitoring the earth-atmosphere system and its resources through the measurement, analysis and interpretation of electromagnetic energy emanating from features of interest.